Contribution to the Flora of the Gir Forest in Saurashtra - Santapau, H.; Raizada, M. B. (Indian Forester, 1954)
The Gir forest, more popularly known as the only remaining home of the Asiatic lion in India, has an area of about 500 square miles. The authors who are concerned with the Gir forest vegetation, studied it in the month of October, when it is rich in herbaceous plants and tall grasses. Teak is the main forest tree which, however, except in specially managed areas consists of crooked trees as a result of maltreatment. Terminalia crenulata is next in importance and then come Wrightia tinctoria, Dalbergia latifolia and Sterculia urens, whereas the gregarious Acacia arabica and Zizyphus nummularia constitute the thorny scrub. Grouped near the villages are the Tamarind, the banyan, Bassia and ornamental trees such as Delonix regia and Erythrina suberosa. Near the Hiran River Saccharum spontaneum is conspicuous. The buffalo population of the Gir is far too much for the available grazing and various regulations have been made to control the numbers. The local shepherds called Maldaris are however, a dwindling race due to incidence of diseases and high degree of sterility. Apparently the people best suited for the conditions are some Negroes who came to India a long time ago Much attention has recently been given by the forest department to conservation of water by means of small dams, over 5,000 in number, and to planting of useful kinds of trees. New plantations of teak, Salmalia malabarica and Terminalias are coming up. Such measures together with control on buffalo population should bring about a good forest growth in the Gir. Appended to the paper is a list of over 400 plant species collected in the area. It is arranged according to the system followed in the Flora of British India and similar works, with the names brought up-to-date as far as possible according to rules of botanical nomenclature. No attempt has been made to give descriptions as these are easily available in standard floras.